Editorial - Grimaldo Muchotrigo, Mirian (2021)
University teaching is often exercised from reflection. That is to say, to think of ourselves from the scientific debates about teaching in higher education and thus promote research. and thus promote research. In the Revista de Investigación en Docencia Universitaria (RIDU) we seek to share the studies of our collaborators and encourage the production of scientific knowledge in our readers. encourage the production of scientific knowledge in our readers. In this sense, and according to the JCR (Journal Citation Reports) ranking of the Web of Science Group (WoS) 2020, we are ranked first in Peru in the category of Education and 156th in the world (Scientific Journal of Communication and Education Comunicar, 2021). This recognition commits us to continue working and exploring the multiple paths of university teaching. the multiple paths of university teaching.